Linear systems of ordinary differential equations, with periodic and quasi-periodic coefficients - Erugin, N. P. (Nikolai Pavlovich) (Mathematics in science and engineering, 1966)
Linear systems of ordinary differential equations, with periodic and quasi-periodic coefficients.